Pengaruh Konsumsi Pisang Ambon Terhadap Peningkatan Kadar HB Ibu Hamil - Achmad Abdul Luftbis; Febi Ratnasari (Sekolah Tinggi Ilmu Kesehatan Yatsi, 2020)
ABSTRACT Background anemia in pregnancy is a health problem that is still often occurs, all pregnant women are required to consume Fe tablets to reduce the incidence of anemia but there are still many pregnant women are still experienced anemia because there are still many pregnant women not compliant in consuming Fe tablets, traditional treatment is the best choice, namely by consuming ambon banana. The purpose of this study was to determine the effect of ambon banana on increasing hemoglobin levels in pregnant women with anemia in the Tigaraksa Puskesmas Regency Tangerang. This research method used Quasi experimental design with the design of Nonequivalent control group design. The population in this study were 78 pregnant women with anemia in the Tigaraksa Puskesmas Regency Tangerang. The sample consisted of 30 respondents consisting of 2 groups 15 intervention groups and 15 control groups. Samples were taken by purposive sampling technique. Data obtained by measuring hemoglobin levels (Easytouch GCHB). The results of the analysis of the data used were univariate and bivariate analysis using paired T-test and produced a P value of 0.001 (P <0.05). Thus, it was stated that there was an effect of giving ambon banana to the increase in hemoglobin levels in the pregnant woman with anemia. The conclusions there was a significant influence in the administration of ambon banana to the increase in hemoglobin levels in pregnant women with anemia. Suggestions are expected for pregnant women with anemia to be able to consume ambon banana 2 fruit in a day to increase hemoglobin levels.